2015
DOI: 10.3892/mco.2015.522
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognosis of breast cancer patients with type 2 diabetes mellitus

Abstract: Abstract. Type 2 diabetes mellitus (T2DM) can increase the risk of several common cancers, including breast cancer (BC). The purpose of the present study was to investigate the clinicopathological features and prognosis of BC patients with or without T2DM. Seventy-eight patients were diagnosed with T2DM prior to the diagnosis of BC in the Cancer Hospital of Shantou University Medical College (Shantou, China) between 2002 and 2008. A total of 300 BC patients without T2DM were randomly selected as study controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The literature regarding the association between diabetes and pathologic breast cancer characteristics is scarce (6,22-27), but the majority is consistent with our findings. These studies also concluded that patients with T2D presented with larger tumors (23,24,26,27), higher rates of lymph node metastasis (22)(23)(24), more advanced stages (22,27), and higher-grade tumors (25). Furthermore, these studies (6,(22)(23)(24)(25)(26)(27) also determined the association between diabetes and hormone receptor status (ER, PR, and HER2).…”
Section: Discussionmentioning
confidence: 94%
“…The literature regarding the association between diabetes and pathologic breast cancer characteristics is scarce (6,22-27), but the majority is consistent with our findings. These studies also concluded that patients with T2D presented with larger tumors (23,24,26,27), higher rates of lymph node metastasis (22)(23)(24), more advanced stages (22,27), and higher-grade tumors (25). Furthermore, these studies (6,(22)(23)(24)(25)(26)(27) also determined the association between diabetes and hormone receptor status (ER, PR, and HER2).…”
Section: Discussionmentioning
confidence: 94%
“…All of the included articles were published from 2001 to 2016. Of the 17 articles, 3 studies [26,28,32] had a prospective cohort design, 10 studies [1723,27,29,30] had a retrospective cohort design, and 4 studies [24,25,31,33] had a case–control design. The total number of breast cancer patients was 48,315, with study populations ranging from 378 to 6342 in the individual articles.…”
Section: Resultsmentioning
confidence: 99%
“…The relative risk for mortality of BC patients has been reported to be twofold greater in BC patients with DM than in those without DM (Liao et al 2011), and the epidemiologic evidences showed that DM patients have a significant higher risk of BC and is closely associated with a poor prognosis of BC patients (Luo et al 2014; Oppong et al 2014). The BC patients with T2DM had been reported to be more likely to associate with a higher incidence of lymph nodes and were at an advanced tumor stage, indicating a shorter survival time (He et al 2015). …”
Section: Introductionmentioning
confidence: 99%